Le rapprochement Chercheur-Consultant en aménagement du territoire : un apport à haute valeur ajoutée ? - Christine Chemin; Emmanuel Thimonier (EchoGéo)
In urban planning new partnership practices seem to appear through the realization of expertises (studies, projects engineering, audits…). Although the appeal to consulting firms – to consultants – and in the scientific laboratories – to researchers – by the State services or local government, exists for a long time now, the partnership between consultants and researchers is recent. Even though this partnership is not systematic in urban planning, it brings a contribution with a high added value in the services, according to the public partners.